Developing graduate profiles through AI-based deep learning training for Social Studies teachers - Ratmaningsih, Neiny; Abdulkarim, Aim; Anggraini, Diana Noor; Sopianingsih, Pitria (Jurnal Abmas, 2026)
Teachers often face several challenges in developing instructional materials, which can impact graduate profiles. The objective of this training is to enhance graduate profiles by implementing AI-based deep learning for social studies teachers. The community service program was implemented using an inductive approach in two phases: direct and indirect training, targeting social studies teachers who are members of the Social Studies teachers’ working group (MGMP IPS) in Bandung City, West Java. The training results indicate that AI-based deep learning through chatbots can integrate the principles of mindful, meaningful, and joyful learning, thereby creating a meaningful learning experience. The success of learning depends on teachers’ attention to students’ potential to ensure an efficient learning process, support self-development, and shape character. The training was conducted continuously by encouraging Social Studies teachers to plan, implement, reflect on, and select learning models, methods, and strategies appropriate to students’ characteristics and curriculum requirements. The outcome of this training is the development of graduate profile dimensions encompassing faith, piety, citizenship, critical thinking, creativity, collaboration, independence, health, and communication—all resulting from deep social studies learning oriented toward strengthening national character.
Keywords: artificial intelligence; deep learning; graduate profile; social studies teacher; training